Uji Aktivitas Antijamur Ekstrak Etanol Daun dan Daging Buah Berenuk(Crescentia cujete, Linn.) terhadapCandida albicans ATCC 1023 - Dewi Sulistyawati; Kartinah Wiryosoendjojo; Nony Puspawati (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Candida albicans is the cause of opportunistic candidiasis which is a fungal infection with the highest incidence. Candidiasis is a disease that can attack the oral cavity, mucous membranes, and genital areas. Indonesia is a country that is rich in biodiversity and people have used more than 6,000 species of plants as medicines and protection needs. One of the herbs that can be used as an alternative treatment for candidiasis is Calabash (Crescentia cujete, Linn.) Which has not been much studied. Throwing contains alkaloids, flavonoids, phenols and tannins which can damage the cell wall of Candida albicans. The purpose of this study was to determine the antifungal activity of leaves and fruit of Calabash (Crescentia cujete, Linn) against Candida albicans ATCC 1023 and determine the maximum concentration as an antifungal. This research is an experimental laboratory research. The test method used is the disk diffusion method. The extraction method used is ethanol maceration. The results showed that the leaves and fruit of Calabash had an antifungal activity against Candida albicans ATCC 1023. The maximum concentration of the extracts of the Calabash was 25% with inhibition zone diameters of 15 ± 0.8 mm and 9.33 ± 0, 57 mm.